2013
DOI: 10.1016/j.ejon.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence mammography screening behaviour: A qualitative study of Greek women's experiences

Abstract: Aim: To identify the factors that influence mammography screening behaviour in a sample of Greek women.Methods/Sample: Data were collected in Athens-Greece, from individuals who were members of six women's associations. A subset of 33 women were interviewed about their screening behaviour and experiences out of the 186 women who completed an initial questionnaire. This paper focuses on the findings revealed from the interviews.Women's associations were approached for the recruitment of the interviewees.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…Related to this finding, Kaltsa, Holloway, and Cox (2013) found that family and close friends influenced women's mammography screening behaviour. Furthermore, in a study of pharmaceutical use in Maputo, Mozambique, Rodrigues (2016) showed that communities' and social networks' experiences with healthcare were an important factor when individuals evaluated and chose between different therapeutic resources.…”
Section: Social Influencesmentioning
confidence: 78%
“…Related to this finding, Kaltsa, Holloway, and Cox (2013) found that family and close friends influenced women's mammography screening behaviour. Furthermore, in a study of pharmaceutical use in Maputo, Mozambique, Rodrigues (2016) showed that communities' and social networks' experiences with healthcare were an important factor when individuals evaluated and chose between different therapeutic resources.…”
Section: Social Influencesmentioning
confidence: 78%
“…On the other hand, the HBM is considered a weak predictor of behaviour change as it does not include the formation of an intention to change behaviour as a precursor to behavioural change, does not accommodate social and environmental influences or past behaviour, and assumes that human decision-making are rational [84]. In response to each model’s limitations, a combination of the two may determine behaviour likelihood [84, 85] and as shown in this study, their combination provided improved prediction of non-attendance (i.e. prediction of non-attendance improved significantly from 38.8% to 65.0% when combining all significant predictors).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, health care providers can use the HBM and CSM to understand patients' needs, employing constructs of the models to guide patient interviewing. For instance, a breast screening invitation may be based on factors that influence BS behaviour such as existing perceptions of benefits and barriers and on psychological and social factors (Kalsta, Holloway & Cox, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Women were recruited from the breast screening centre and were breast screening attendees, aged 50-60 years. The convenience sample was recruited because it was felt that such women would be interested in engaging with such a Translation and adaptation of scales for breast screening among Maltese women 7 topic (Creswell & Plano Clark, 2011), thereby giving access to a range of women with different backgrounds (Kalsta, Holloway & Cox, 2013). Women with prior history of breast cancer or breast surgery, those who sought breast cancer treatment as well as non-bilingual women were excluded.…”
Section: Sample and Proceduresmentioning
confidence: 99%